Integration of lean and green manufacturing to speed up the automotive parts production process for sustainability orders from customers - Kurnia, Hibarkah; Sulaeman, Asep Arwan; Pasha, Vebina Sheila (Universitas Serang Raya, 2024)
Fulfilling orders from the automotive industry customers is a necessity. Problems arising from product delivery to customers are due to production delays, decreased production yields, and environmental pollution caused by production waste. The production process often experiences wasted time producing four-wheeled vehicle spare parts and a high percentage of production defects. This research aims to reduce production process time, provide solutions to reduce waste, and balance production stock according to customer orders. This research uses the Lean Manufacturing (LM) approach with the Value Stream Mapping (VSM) method combined with the Green Manufacturing (GM) approach with the Just in Time (JIT) and Kanban methods. This research resulted in the production process time for four-wheeled vehicle spare parts decreasing from 11.0 days to 4.5 days, meaning a decrease of 159%. It affected production results, increasing from average monthly production of 42,917 pcs to 59,990 pcs, meaning an increase of 128%. Meanwhile, the shipment plan target has been achieved at 96% of the plan order. Meanwhile, Turn Over Inventory (TOI) results are under 30 days, so customer order continuity exists.